Roads to discovery - Lapp, Ralph E. (Harper, 1967)
This is a valuable book for the interested layman, teacher and student. It makes clear all the fundamentals of atomic science in a way that should make it one of the first books to be consulted for a broad picture of the theoretical and technological development, and potentiality of nuclear physics.